Fine-Needle Aspiration Cytology of Ewing’s Sarcoma of Thoracic Spine with Extension into the Intradural Space - Sandhya Bordia; Sweta Meena; Bijendar Kumar Meena; Vijay Rajak (Case Reports in Oncological Medicine)
Ewing’s sarcoma/peripheral primitive neuroectodermal tumor is a small, round, and blue cell malignancy that occurs most often in bone and soft tissues of children and young adults. The intraspinal manifestation of the disease is rare, and when present, this is often misdiagnosed with other varieties of primary spinal tumors. Fine-needle aspiration cytology (FNAC) plays important role in the early diagnosis of these cases. We report such a case of Ewing’s sarcoma of thoracic spine with extension into the intradural space, which was initially suspected to be a case of metastatic lesion in an 18-year-old boy.